The whole time - Bybee, Catherine (Bybee, Catherine. D'Angelos series, 2023)
From New York Times and USA Today bestselling author Catherine Bybee comes a tale of a strong-willed dancer exercising her independence and the rich biker she can't let go. Salena Barone has broken free of her family and moved into an apartment above the D'Angelos' restaurant, where she works as a manager--without a husband, thank you very much. But even on a restaurant salary, she soon finds herself strapped for cash. Salena's never been afraid of living on the wild side, though, so she takes on a side hustle that'll raise big bucks...and eyebrows, if anyone finds out. Tattooed biker Ryan is the youngest of the wealthy Rutledge wine family and has never dreamed of rings, forever, or continuing the family business. He's perfectly happy living his own life and helping out hardworking folks in his own way. When these two independent singles spot each other at a Rutledge-D'Angelo wedding, the attraction is instant. But as their friendship with benefits evolves into something more, the secrets Salena's keeping--from family, friends, and Ryan--threaten the happily ever after she never knew she wanted.